Free Exercise in the Free State: Maryland's Role in Religious Liberty and the First Amendment - Lasson, Kenneth (A journal of church and state, 1989)
Kenneth Lasson; Free Exercise in the Free State: Maryland's Role in Religious Liberty and the First Amendment, Journal of Church and State, Volume 31, Issue 3,